Ranking Stressors and Coping Hierarchies in Families Facing Financial Instability - Chaiyasit, Kittipong; Al-Obaidi, Zainab; Meier, Johanna (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to identify, categorize, and rank the primary stressors and coping hierarchies experienced by families facing financial instability using a mixed-method exploratory approach.Methods and Materials: The research followed a sequential mixed-method design. In the first phase, a qualitative literature-based analysis was conducted to identify core themes and subthemes related to financial distress and coping strategies. Data were extracted through a systematic literature review and analyzed thematically using NVivo 14 software until theoretical saturation was reached. Six main thematic categories emerged from the analysis: economic stressors, emotional and psychological strain, family relationship dynamics, coping strategies and hierarchies, social and community support, and adaptive resilience processes. In the second phase, a quantitative ranking was performed among 210 participants from Iraq selected through purposive sampling. Data collection employed a structured questionnaire derived from qualitative results. SPSS version 26 was used to perform Friedman’s test and Kendall’s coefficient of concordance (W) to determine the statistical ranking and consistency of participants’ responses.Findings: The analysis revealed significant differences across the six thematic domains (χ² = 112.47, p < 0.001; W = 0.71). Economic stressors received the highest mean rank (4.58), followed by emotional and psychological strain (4.44) and family relationship dynamics (4.27). Coping strategies and hierarchies (4.05) and social and community support (3.86) followed, while adaptive resilience processes ranked lowest (3.54). The strong Kendall’s coefficient indicated a high level of agreement among respondents, confirming a shared perception of financial instability as a multidimensional challenge with economic and emotional dimensions.Conclusion: The study demonstrated that financial instability generates complex, hierarchical stress patterns within families, with economic hardship triggering psychological strain and relational tension. Enhancing both structural financial security and emotional resilience is essential for sustainable family adaptation.